ANALYSIS OF FACTORS AFFECTING DESIRES MUSEUM VISITING AND ITS IMPLICATIONS FOR STRATEGY MUSEUM MARKETING - Agus Leo Handoko (Adisam Publisher, 2024)
The museum is a permanent institution and does not seek profit. In the last two decades, museums have experienced a paradigm shift, from being oriented towards collections, becoming oriented towards visitors. Museums are required to provide the best service to attract visitors from an educational and recreational perspective. An aspect that needs to be considered in the context of changes in museum management is the need for marketing. So that the museum can be known to the public and become an alternative place for tourists to spend their free time. Marketing strategy is delivering products to visitors, so that the marketing carried out is able to attract visitors to visit the museum. Museums must be able to present themselves with creative packaging so that the visiting public does not conclude that the museum is not a place to display objects or culture that is dead (frozen culture). Museums must show that what they exhibit is closely related to actual life today. Therefore, it is necessary to have an appropriate and targeted marketing strategy in order to attract tourists to want to visit. The marketing strategy carried out must pay attention to the strengths and weaknesses of the Museum. The marketing strategy that will be determined is two-sided, namely online and offline.